A quasi-experimental study provides evidence that registered dietitian nutritionist care is aligned with the Academy of Nutrition and Dietetics evidence-based nutrition practice guidelines for type 1 and 2 diabetes - Lamers-Johnson, Erin; Kelley, Kathryn; Knippen, Kerri Lynn; Feddersen, Kimberly; Sánchez, Damien M.; Parrott, J. Scott; Colin, Casey; Papoutsakis, Constantina; Jimenez, Elizabeth Yakes (Frontiers in Nutrition, 2022)
Background:  One previous study examined implementation of evidence-based nutrition practice guidelines (EBNPG). Objectives: To describe alignment of registered dietitian nutritionists' (RDNs) documented nutrition care with the Academy of Nutrition and Dietetics’ EBNPG for diabetes and examine impact of a midpoint training on alignment with the guideline. Methods: In this two-year, quasi-experimental study, nineteen RDNs providing outpatient medical nutrition therapy to adults with diabetes (n=562) documented 787 encounters. At study midpoint, RDNs received a guideline content training. A validated, automated tool was used to match standardized nutrition care process terminology (NCPT) in the documentation to NCPT expected to represent guideline implementation. A congruence score ranging from 0 (recommendation not identified) to 4 (recommendation fully implemented) was generated based on matching. Multilevel linear regression was used to examine pre-to-post training changes in congruence scores. Results: Most patients (~75%) had only one documented RDN encounter. At least one guideline recommendation was fully implemented in 67% of encounters. The recommendations “individualize macronutrient composition” and “education on glucose monitoring” (partially or fully implemented in 85% and 79% of encounters, respectively) were most frequently implemented. The mean encounter congruence scores were not different from pre-to-post guideline training (n=19 RDNs, 519 encounters pre-training; n=14 RDNs, 204 encounters post-training; β=-0.06, SE=0.04; 95% CI: -0.14, 0.03). Conclusions: Most RDN encounters had documented evidence that at least one recommendation from the EBNPG was implemented. The most frequently implemented recommendations were related to improving glycemic control. A midpoint guideline training had no impact on alignment of care with the guideline.